2017
DOI: 10.3390/geosciences7040136
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Geographically Weighted Regression in Modeling Human Leptospirosis Based on Environmental Factors in Gilan Province, Iran

Abstract: It is of little debate that Leptospirosis is verified as the most important zoonosis disease in tropical and humid regions. In North of Iran, maximum reports have been dedicated to Gilan province and it is considered as an endemic problem there. Therefore, modeling or researching about different aspects of it seems indispensable. Hence, this paper investigated various models of Geographically Weighted Regression (GWR) approach and impacts of seven environmental variables on modelling leptospirosis in Gilan. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…This, in turn, has fostered the utilization of GIS analytics and geospatial statistics for environmental analyses of infectious diseases [14]. Previous studies have adopted GIS analysis tools in the study of ecological models to explore and analyse spatial variations in relationships between local environmental factors and the occurrences of leptospirosis [13,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis 21 [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…The Global Epidemic and Mobility Model, validated by empirical surveillance during the 2009 H1N1 pandemic, uses a spatial layer of population distribution coupled with a transportation network layer and a flexible manipulated model of disease transmission to predict epidemic spread that is accurate against a gold standard [37]. Various geographically weighted regression models can now tell us where to deploy leptospirosis prevention programs [38], for example, with greater spatial resolution and resource efficiency. Scan statistics, hot spot analysis and Poisson kriging (forms of cluster analysis and interpolation, respectively) can highlight incidence clusters of cardiac arrest for intervention programs ranging from bystander CPR trainings to AED placement [39, 40].…”
Section: Why Geospatial Analysis Is Good For Humanitarian Healthmentioning
confidence: 99%